The political economy of renewable energy policies in Germany and the EU. (October 2016) - Strunz, Sebastian; Gawel, Erik; Lehmann, Paul
Abstract: In this paper, we employ a public choice perspective to analyze the development of policies for renewable energy sources (RES) in the EU in general and in Germany more specifically. In doing so, we explain the main characteristics of current RES policies by reference to the self-interest driven motivations of voters, stakeholders and political actors. One important puzzle, which we address, is the following: How could effective RES-policies be introduced against the political opposition of fossil-fuel interest groups in the past? Via analyzing the German example in more detail, we show how over time a self-reinforcing interplay of ideological and financial RES support has emerged. Moreover, we argue that observed specific design choices for RES policies in Germany, such as largely riskless remuneration schemes and high degrees of technology differentiation, as well as decentralized decision-making across EU Member States, can be traced back to politicians' need to balance a variety of partly opposing interests. A major benefit of the presented analysis is that it provides a realistic assessment of the challenges for RES policy reform – any reform effort critically depends on its ability to balance stakeholder interests. Highlights: Support policies for renewables are driven by politico-economic incentives. The specific design of support policies results from the need to balance competing interests. A self-reinforcing interplay of ideological and financial support has emerged. National policy making is strongly affected by actors on both EU and sub-national level.